1986
DOI: 10.1149/1.2109057
|View full text |Cite
|
Sign up to set email alerts
|

High Yield Luminescence of Lanthanide J‐Levels in Fluoride Glasses with Weak Multiphonon Relaxation

Abstract: Glasses prepared from mixed fluorides containing trivalent lanthanides show a unique propensity to luminescence of a given J‐level, if the distance to the closest lower J‐level is at least 2,000 cm−1 (to be compared with 5,000–10,000 cm−1 in most other materials).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…They reported a resonant energy transfer from the 1 D 2 Tm 3ϩ state to the 5 D 4 Tb 3ϩ state. Jorgensen et al 161 found high yield luminescence of lanthanide J-levels in fluoride glasses with weak multiphonon relaxation.…”
Section: Survey Of Luminescence Papers Published In the Journal In Th...mentioning
confidence: 99%
“…They reported a resonant energy transfer from the 1 D 2 Tm 3ϩ state to the 5 D 4 Tb 3ϩ state. Jorgensen et al 161 found high yield luminescence of lanthanide J-levels in fluoride glasses with weak multiphonon relaxation.…”
Section: Survey Of Luminescence Papers Published In the Journal In Th...mentioning
confidence: 99%